A note on the arc elasticity of demand - Vázquez, Andrés (Estudios Económicos de El Colegio de México, 1995)
This note presents a simple alternative measure for the arc elasticity of demand which comes naturally and does retain the salient characteristics of the point demand elasticity. A remarkable feature is that it equals the point demand elasticity at some point inside the interval, thus leading to the exact estimation of the point demand elasticity when this is constant. It also ensures that the relationships between the arc demand elasticity and the arc revenue elasticities keep exact formal analogy with those well-known for the point elasticity case.